Teachers’ Learning Loss Diminution Through Self-Phased Learning with Guru Binar - Kisno Kisno; Calen Calen; Mega Romauly Tampubolon; Tiodor Sri Manalu; Richard Berlien; Khesara Niros Gulo; Adam Kešner (Indonesian Journal of Educational Studies, 2021)
The emergence of Covid-19 worldwide has disrupted education activities. Massive Open Online Courses (MOOC) turned up as the alternative of online learning. However, MOOC did not always guarantee the success of online learning. Learning loss during online learning was experienced both by students and teachers during this pandemic situation was unavoidable. The objective of this research to find put how Guru Binar as an MOCC managed to reducing teachers’ learning loss. A qualitative method was implemented using a structured-interview among selected Guru Binar users from different educational institutions in Indonesia such as primary and secondary schools. There were totally three focus group discussions and eight Guru Binar users were involved in these FGD.  The results pointed out that this self-phased learning platform was able to diminish teachers’ loss time through interactive talkshow or webinars and the online classes aided its users in spending proper time with innovative games. Keywords: Learning Loss, Massive Open Online Course, Self-Phased Learning